Estimating elbow loading conditions through the motion behaviors of subchondral bone density during joint movements - Satoshi Miyamura; Ryoya Shiode; Toru Iwahashi; Arisa Kazui; Natsuki Yamamoto; Tasuku Miyake; Seiji Okada; Tsuyoshi Murase; Kunihiro Oka; Hiroyuki Tanaka (Scientific Reports)
Abstract Evaluating complicated stress across the elbow under joint motion remains difficult. Here, we aimed to evaluate the distribution of the subchondral bone density in the normal elbow bones and further characterize their spatial relationships during elbow motion to estimate the loading stress across the articular surface using three-dimensional computed tomography bone models. The normal elbow joint exhibited a consistent distribution pattern of subchondral bone density. High-density regions were distributed in the capitellum and posterior humeral trochlea, sagittal ridge of the ulnar trochlear notch and ulnar-volar side of the radial head. Motion analyses revealed that the high-density regions proximate with elbow flexion with forearm pronation in the radiocapitellar joint and in the fully extended position in the ulnohumeral joint. This reasonably reflects the stress acting on the joint surface under actual loading conditions. These findings suggest that daily activities involving lifting or carrying objects in these positions are stress-prone activities.